Crystal structure of [(4-bromobenzyl)triphenylphosphonium] tetrabromidoindium(III), [C25H21BrP]+[InBr4]− - Li Xue; Wang Guangyao (Zeitschrift für Kristallographie - New Crystal Structures)
C25H21Br5PIn, monoclinic, P21/c (no. 14), a = 10.5887(2) Å, b = 14.7713(2) Å, c = 18.9737(3) Å, β = 102.300(2)°, V = 2899.53(8) Å3, Z = 4, Rgt(F) = 0.0450, wRref(F2) = 0.1205, T = 293(2) K.